Learning a motor action "From Within": Insights into perceptual-cognitive changes with mental and physical practice - Frank, C. (Sport and exercise psychology research: From theory to practice, 2016)
The two most common means to (re)learn a motor action are through physical practice (ie, repeatedly executing a motor action) and mental practice (ie, repeatedly imagining the execution of a motor action). Both types of practice have shown to lead to permanent improvements in motor performance as well as to functional reorganization within the brain. However, little is known about the learning of a motor action as induced by both mental and physical practice from a perceptual-cognitive perspective. The goal of the present chapter is to explore the topic from this perspective with a particular focus on the representation of complex action as well as gaze behavior and their development during early skill acquisition. To this end, a line of research systematically investigating the influence of mental and physical practice on the development of novices` mental representations and "quiet-eye" behavior in golf putting is presented, thereby providing insights into the perceptual-cognitive adaptations that occur within the motor action system according to practice type. Finally, the relevance of this perspective, particularly for motor learning, motor imagery, and quiet-eye research is discussed. (übern.)